The Penerapan Flipbook Berbasis CIRC terhadap Sikap Kritis dan Pemahaman Membaca Teks Pidato Siswa Kelas V - Sitompul, Yohana P.; Purwati, Panca Dewi (YASIN, 2025)
Although the use of digital media in learning has been widely addressed in previous studies, research that specifically examines the integration of a flipbook based on the Cooperative Integrated Reading and Composition (CIRC) model to enhance critical attitudes and reading comprehension remains limited. This study aimed to describe the implementation of the flipbook-based CIRC model, evaluate its effectiveness in developing critical attitudes, and analyze improvements in reading comprehension among fifth-grade students at SDN 7 Boja, Kendal Regency. A mixed-methods approach with a sequential exploratory design was employed, involving 24 students selected through saturated sampling. Data were collected through observation, interviews, documentation, and written tests (pretest and posttest), and were analyzed using the Miles and Huberman model for qualitative data, as well as N-Gain analysis and descriptive statistics for quantitative data. The findings show that most students achieved the “very good” category in terms of critical attitude, and that the average reading comprehension score increased by 30.04 points with an N-Gain score of 0.59 (medium category); the percentage of learning mastery also rose sharply from 4.16% to 83.3%. These results extend understanding of the effectiveness of integrating interactive digital media with cooperative learning models in language instruction and underscore the importance of using CIRC-based flipbooks to enhance text analysis skills and literacy quality among elementary school students. The study concludes that the flipbook-based CIRC model is effective in developing critical attitudes and reading comprehension, with theoretical implications for the development of Indonesian language learning design and practical implications for teachers and schools in utilizing digital media as a student-centered instructional strategy.